WEB-BASED LPG DISTRIBUTION MANAGEMENT INFORMATION SYSTEM AT PT BOY BAGUS WINDI - Dwi Silviana; Samsudin; Raissa Amanda Putri (Department of Computer Engineering, Universitas Wiralodra, 2023)
PT Boy Bagus Windi is one of the LPG distributors in the Langkat Regency. Because Microsoft Excel is still used to hold distribution data, financial data, sales and purchase data, and personnel data, PT. Boy Bagus Windi faces a number of difficulties managing his data. The problem that businesses run into is that when they need to look for data, it takes a while since they have to access each folder or page in Microsoft Excel individually. Due to the current rapid growth of information technology, many businesspeople conduct their everyday activities online. In order to administer its business management information system, a company is compelled to adopt a web-based information system. Therefore, PT. Web-based Boy Bagus Windi developed a management information system. This system is intended to make it simpler for businesses to search data and handle human, financial, and products data management in one web for a more streamlined and orderly arrangement.